Pengaruh Lingkungan Kerja, Beban Kerja, dan Kepuasan Gaji Terhadap Kinerja Karyawan (Studi Kasus Pada Jack Runner Roastery di Kota Bandung) - Pratiwi, Dinda Intan; Priyono, Achmad Agus; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract In the Jack Runner Roastery coffe shop in Bandung, this research investigates how the work environment, workload, and salary satisfaction influence employee performance. This research was conducted quantitatively using multiple linear regression analysis. Data was collected through questionnaires distributed to 32 staff members as research samples. The research result show that employee performance is significantly influenced by the work environment, workload and salary satisfaction. This shows that these elements increase the productivity and effectiveness of employee performance.These findings have implications for company management in developing better strategies to improve employee performance. A more comprehensive approach is needed in managing human resources, including increasing employee motivation and welfare. In addition, this researcher contributes to the human resource management literature by showing that work environment, workload and salary satisfaction are important factors in increasing productivity. Future research is recommended to examine other factors such as leadership and organizational culture that may further influence employee performance in the service industry.  Keywords : Work Environment, Workload, Salary Satisfaction, Employee Performance, Jack Runner Roastery